1997
DOI: 10.1046/j.1471-4159.1997.69052048.x
|View full text |Cite
|
Sign up to set email alerts
|

Amidation of β‐Amyloid Peptide Strongly Reduced the Amyloidogenic Activity Without Alteration of the Neurotoxicity

Abstract: /3-Amyloid accumulates in cerebral deposits in Alzheimer's disease, so to test the correlation between the neurotoxic and fibrillogenic capacity of /3-amyloid, we synthesized a peptide homologous to fragment 25-35 of /3-amyloid (/325-35) and amidated at the C-terminus (/325-35-NH 2). As the amidation strongly reduced the amyloidogenic capacity of /325-35, we compared its neurotoxic activity in the amidated (/325-35-NH2) and nonamidated forms. The viability of primary cultures from fetal rat hippocampus was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The observation that the amidated form of A␤ 25-35 was less potent in inhibiting APP secretion agrees with previous studies that have shown that amidation prevents fibrillation of A␤ (Forloni et al, 1997). A␤ peptides modified by cyclization of N-terminal residues are deposited in the brain and are known to form stable water-soluble aggregates (Mori et al, 1992;Saido et al, 1995Saido et al, , 1996Kuo et al, 1997;Russo et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observation that the amidated form of A␤ 25-35 was less potent in inhibiting APP secretion agrees with previous studies that have shown that amidation prevents fibrillation of A␤ (Forloni et al, 1997). A␤ peptides modified by cyclization of N-terminal residues are deposited in the brain and are known to form stable water-soluble aggregates (Mori et al, 1992;Saido et al, 1995Saido et al, , 1996Kuo et al, 1997;Russo et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
“…1B), whereas [pyroglu 11 ]A␤ 11-40 caused a 10% increase in cell-associated [ 35 S]APP. The amidated form of A␤ 25-35 (A␤ 25-35 NH 2 ), which has previously been shown not to form fibrils and to be less toxic than the A␤ 25-35 free acid (Forloni et al, 1997), decreased [ 35 S]APP secretion by only 26% and did not measurably affect levels of cell-associated [ 35 S]APP (Fig. 1B).…”
Section: Effect Of A␤ Peptides On App Secretionmentioning
confidence: 93%
“…It is furthermore speculated that amidation of the C-terminus has an effect on the aggregation propensity of the IAPP peptide [17]. Similar effects have as well been reported for other amyloidogenic peptides [36].…”
Section: Introductionsupporting
confidence: 69%
“…This is widely recognized as the culprit in the disease on the basis of cellular and animal models of AD and familial cases of AD and Down's syndrome. The initial amyloid hypothesis, stating that highly aggregated fibrils of b-amyloid were responsible for neurotoxicity, was questioned by the demonstration that smaller, soluble aggregates induced neuronal cell death (Forloni et al 1997). These species, subsequently called Ab oligomers, have more recently emerged as the main toxic forms responsible for synaptic dysfunction and cognitive impairment (Walsh and Selkoe 2007;Klyubin et al 2008;Balducci et al 2010a).…”
Section: Introductionmentioning
confidence: 99%